Palladium Nanoparticles Supported on Magnesium Hydroxide Fluorides: A Selective Catalyst for Olefin Hydrogenation. Issue 11 (11th September 2014) - Acham, Vaibhav R.; Biradar, Ankush V.; Dongare, Mohan K.; Kemnitz, Erhard; Umbarkar, Shubhangi B.
Abstract A one‐pot synthesis of palladium nanoparticles supported on magnesium hydroxide fluoride has been performed with the fluorolytic sol–gel method. The prepared catalysts were characterized by using various physicochemical techniques. The sol–gel method led to high surface area (>135 m2 g−1), mesoporous catalysts (pore volume=0.19–0.23 cm3 g−1, pore diameter=3–5 nm) with uniformly dispersed palladium nanoparticles approximately 2 nm in diameter on the surface. The catalysts synthesized by using different concentrations of aqueous hydrofluoric acid exhibited changing surface and acidic properties. Very high dispersion of palladium on magnesium fluoride (47 %) was obtained with 1 wt % palladium loading. The catalysts were used for hydrogenation of various olefins in the presence of other organic functionalities at room temperature and atmospheric hydrogen pressure. Various substituted olefins were hydrogenated with almost 100 % conversion and selectivity. The catalysts were recycled efficiently over five cycles without appreciable loss in catalytic activity. There was no palladium leaching under the reaction conditions, which was confirmed by inductively coupled plasma atomic emission spectroscopy analysis. Activation of olefin on the catalyst surface could not be observed by in situ FTIR studies, indicating facile activation of hydrogen on the palladium supported on magnesium hydroxide fluoride.